2020
DOI: 10.21203/rs.3.rs-52752/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-Reported Taste and Smell Disorders in Patients with COVID-19: Distinct Features in China

Abstract: Background: Last December 2019, a cluster of viral pneumonia cases identified as coronavirus disease 2019 (COVID-19), was reported in Wuhan, China. We aimed to explore the frequencies of nasal symptoms in patients with COVID-19, including loss of smell and taste, as well as their presentation as the first symptom of the disease and their association with the severity of COVID-19.Methods: In this retrospective study, 1,206 laboratory-confirmed COVID-19 patients were included and followed-up by telephone call on… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…al. 6 , and self-reported by patients in a retrospective study conducted early in the pandemic 24 . Other symptoms experienced by Sudanese patients were sore throat and headache.…”
Section: Discussionmentioning
confidence: 99%
“…al. 6 , and self-reported by patients in a retrospective study conducted early in the pandemic 24 . Other symptoms experienced by Sudanese patients were sore throat and headache.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 80% of all COVID-19 patients with smell and taste impairment are reported to regain their sense of smell and taste impairment within 2 weeks of the COVID-19 cure. 65…”
Section: Hypogeusia and Hyposmiamentioning
confidence: 99%
“…The study from China reported 5%-25% patients have smell and/or taste disorder(Jia Song et al 2021;Mao et al 2020). Omicron variant, which firstly detected in South Africa in November 2021, has become the main epidemic strain in the world by 15 January 2022 (Menni et al 2022;Hu et al 2022).…”
Section: Introductionmentioning
confidence: 99%